Enhanced capacitive performance of cathodically reduced titania nanotubes pulsed deposited with Mn 2 O 3 as supercapacitor electrode - Muhammad Muzakir, Muhammad; Zainal, Zulkarnain; Lim, Hong Ngee; Abdullah, Abdul Halim; Bahrudin, Noor Nazihah (Royal Society of Chemistry, 2021)
A facile and simple pulse electrodeposition method was employed to deposit Mn2O3 nanoparticles on cathodically reduced titania nanotubes (R-TNTs) at different deposition time in the range of 3-15 min to investigate the influence of mass loading of Mn2O3 on the electrochemical performance of Mn2O3/R-TNTs nanocomposite for supercapacitor application. Mn2O3 nanoparticles were deposited on circumference of R-TNTs as well as in the nanotubes as revealed by FESEM images for all the deposited time. XPS result confirmed the presence of MnO2 (Mn4+) and MnO (Mn2+) on the Mn2O3/R-TNTs composite which provide pseudocapacitive behaviour for the electrode. Mass loading of Mn2O3 increased linearly with deposition time as confirmed by EDX analysis. The sample deposited for 12 min exhibits the highest areal capacitance of 51 mF cm-2 (which is 22 times enhancement over R-TNTs) at a current density of 0.1 mA cm-2 and specific capacitance of 325 F g-1 at 6 A g-1. The sample also show a high-rate capability by retaining 80% of its capacitance even at higher current density of 30 A g-1. Interestingly, it retained 98% of the capacitance over 5000 charge discharge cycles at 10 A g-1 after initial drop to 95% at 200th cycles suggesting an excellent long-term chemical stability. A considerably low equivalent series resistance (ESR) and charge transfer resistance (R ct) of 9.6 Ω and 0.4 Ω respectively was deduced from electrochemical impedance spectroscopy (EIS) analysis indicating good conductivity and improved charge transfer efficiency of Mn2O3/R-TNTs nanocomposite.